2009
DOI: 10.1080/20786204.2009.10873855
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological profile of non-daily smokers in South Africa: implications for practice

Abstract: Background: This study sought to provide an epidemiological profile of non-daily (ND) smokers in South Africa.Methods: Using data obtained from the 1998 South African demographic and health survey (SADHS) -the largest nationally representative dataset available -smokers were classified as non-daily (ND) smokers or daily smokers. NDS were defined as persons aged 18 and over who had ever smoked 100 cigarettes, but did not currently smoke daily.Results: In 1998, an estimated 10% of current smokers were ND smokers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
(33 reference statements)
0
0
0
1
Order By: Relevance
“…44 Therefore, they may not have the intention to quit their occasional smoking. 7,4,45 On the other hand, there is a claim that non-daily smokers are more prone to quit smoking in the coming months compared with daily smokers. 32 There is a group of non-daily smokers called "converted nondaily smokers".…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…44 Therefore, they may not have the intention to quit their occasional smoking. 7,4,45 On the other hand, there is a claim that non-daily smokers are more prone to quit smoking in the coming months compared with daily smokers. 32 There is a group of non-daily smokers called "converted nondaily smokers".…”
Section: Discussionmentioning
confidence: 99%
“…3 Non-daily smokers are usually younger and more educated and have a higher income than daily smokers. 4 Studies have shown that non-daily smokers often consider themselves as a non-smoker 5,6 ; a belief that might be negatively associated with a person's recent/future attempts to quit smoking. 7 A significant number of nondaily smokers become daily smokers over time.…”
Section: Introductionmentioning
confidence: 99%
“…Yaşamı boyunca hiç sigara içmemiş olanlar "sigara içmeyen" ve daha öncesinde sigara içen ama en az 6 aydır sigara içmeyen kişiler "sigarayı bı-rakmış" olarak sınıflandırıldı. 10,11 Çalışma gruplarının sayısının eşit olması için ardışık olarak çalışmaya alınan kişiler uygun gruplara alınarak grup sayıları yirmiye tamamlandı. Kan alın-ması işlemi sekiz saat açlık sonrasında oturur pozisyondayken, ante-kübital venden hemoreolojik ölçümler için 4 cc venöz kan, 2 adet EDTA'lı kan sayımı tüpüne alındı.…”
Section: Gereç Ve Yöntemunclassified